Role of radiotherapy in the management of heterotopic ossification (Indian Journal of Case Reports, 2024)
Heterotopic ossification (HO) is a process of pathological bone formation in non-osseous tissue. Frequently, it is a complication that occurs from various causes such as traumatic, neurogenic, or genetic disorders, where trauma is the most common cause. HO is of major concern as it can lead to functional disorders, pain, and even to joint ankylosis. Non-steroidal anti-inflammatory drugs and radiotherapy (RT) are preferred in the treatment of HO. RT serves as an important modality for the management of HO because RT potentially inhibits osteoprogenitor cell proliferation. This is a case report of an 18-year-old girl, who developed grade 4 HO at her right hip joint following a fall from height. She, then, underwent excision of heterotopic bone and RT to the right hip joint at a dose of 8 gray (Gy) delivered in 1 fraction, within 48 h of excision. The patient did not report any acute adverse effects related to RT and demonstrated clinical improvement in her range of motion without any recurrence of HO at her 3 and 6-month follow-ups.